γGT and PCSK9 variants in subjects with hyper-LDL-cholesterolemia - Kotani, Kazuhiko; Hamasaki, Masato; Kapse, Snehal (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Gain-of-function (GOF) variants of proprotein convertase subtilisin/kexin type 9 (PCSK9) gene cause high blood low-density lipoprotein (LDL) cholesterol and PCSK9 levels, which are respectively the markers of cardiovascular disease (CVD). High blood activity of gamma-glutamyl transpeptidase (γGT), a pro-oxidant induced by oxidative conditions, is also a marker of CVD. There may be an association between γGT and PCSK9 variants. We aimed to examine the γGT activity by a GOF variant, p.E32K, of PCSK9 in subjects with hyper-LDL-cholesterolemia, an at-risk state for CVD.Methods: This study enrolled 114 subjects (mean age, 59 years; 38 males) with hyper-LDL-cholesterolemia who underwent a genotype assay for identification of p.E32K variant and enzymatic measurement of γGT activity. The relationship between the γGT activity and p.E32K was analyzed.Results: γGT activity was significantly lower (median, 21 IU/L) in subjects with p.E32K (n = 12) than in those without the variant (30 IU/L, P < 0.05). The results remained confirmed by multivariate-adjusted analysis.Conclusions: An inverse association was found between γGT and p.E32K, a GOF variant. Elucidation of the mechanism for their association may help understand the development of CVD by PCSK9 variants.